The impingement factors of the rural library services usage among rural youth in Malaysia - Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva (Canadian Center of Science and Education, 2012)
Developing the rural community is one of the main government agendas. One of the methods used by the government to develop the rural community is by ensuring continuous delivery of information. In tandem with this, many high impact projects for the rural community have been introduced particularly on ICT. Nonetheless, besides ICT, the government also has rural library to rely on. In a number of local and international studies, rural library has been proven to benefit the rural community. The main query of this study is to identify the impingement factors of the rural library usage among rural youth and the findings obtained are expected to contribute to the existing literatures. Using a qualitative method, focus group discussions (FGDs) have been carried out among two groups, one of the FGDs was conducted with six librarians and another FGD was conducted among six rural library users. The FGDs were conducted in Kuala Terengganu, Terengganu, Malaysia. Data gained were later transcribed verbatim and analysed. Based on the analysis done, a total of eight main factors that can impinge their usage of rural library services have been identified. In order to further enhance the usage of rural library services among youth, this study suggests that issues such as relevant sources and activities, youth involvement in the planning process, a better way of promotion and roles of librarians should be highly considered.